The first record of the genus Uncobracon Papp from China (Hymenoptera: Braconidae) - Tan, Jiang-Li; Sheng, Mao-Ling; van Achterberg, Kees; Sun, Shu-Ping (Zootaxa, 2012)
The small genus Uncobracon Papp, 1996 (Hymenoptera: Braconidae: Braconinae), and Uncobracon pappi (Tobias, 2000)comb. nov., are recorded and illustrated from China for the first time. Uncobracon pappi was reared from a borer in the branch of Hippophae rhamnoides Linnaeus ssp. sinensis Rousi. A key to species of the genus Ucobracon is included.